Development of QSAR Model of Caffeic Acid Phenethyl Ester as Anti-Cancer HT-29 - Uripto Trisno Santoso (Jurnal Sains dan Terapan Kimia, 2022)
Caffeic Acid Phenethyl Ester (CAPE) compounds are potentially colorectal anticancer drugs. QSAR (Quantitative Structure-Activity Relationship) research on the CAPE compound class has been carried out, but the model in the previous study did not meet the goodness of fit criteria. The development of the CAPE compound QSAR model as a colorectal anticancer was carried out to obtain a model that meets the goodness of fit criteria and is valid. Eighteen CAPE compounds were used to build the QSAR model using the Multiple Linear Regression (MLR) technique. The descriptor selection was carried out using the backward elimination method and the validation test using the internal leave one out (LOO) cross-validation. The results showed that the QSAR model with four descriptors, namely MDEC22, MDEC23, JGI1, and molecular weight (BM), met the goodness of fit and Q2(LOO) criteria. The development of the QSAR model by adding the LogP descriptor resulted in the QSAR 5 descriptor model with higher goodness of fit level than the QSAR model without the LogP descriptor. Both of these QSAR models have the potential to be used as predictors in the development of a new class of CAPE compounds as anticancer agents against HT-29 cells.